The effect of an 8-month exercise program on bone density and some physical characteristics in sedentary women - Sedef Kurt; Serkan Hazar (Türk Spor ve Egzersiz Dergisi)
The aim of the study was to determine and evaluate the effect of an 8-month step-aerobic and run-walk exercise on bone density and some physical characteristics as weight, total fat mass, total fat percentile and lean mass at sedentary females  14 sedentary females with mean age 37.4 voluntarily participated in the study. Subjects performed an exercise program lasted an hour three days a week for eight months. Exercise program consisted of 45/50- minute step-aerobic one day a week; 30- minute run/walk and 30- minute stretching two days a week. Total bone mineral density (BMD), total bone mineral content (BMC), T score, Z score, Total lean mass, total fat mass and total fat percentile values were diagnosed by dual X-ray absorptiometry (DXA) (Norland XR-46). Wilcoxon signed rank test was used for data evaluation and significance level alpha was set at 0.05. After the eight -month exercise program, it was found out that there was significant decrease in weight, BMI, and total fat mass (p lt;0.05). But the decreases in total fat percentile and lean mass were statically insignificant. Nevertheless the increasing in total BMD, T-score and Z-score were statically significant (p lt;0.05), while the decreases in total BMC value were statically insignificant.  In conclusion the eight-month step-aerobic, run-walk and stretching exercises positively affected some anthropometric components as weight, BMI, and total fat mass. However the program didn’t affect bone mineral contend in a positive way. But the program provides a preventive effect on bone density. It is suggested that preparation of exercise programs with similar purpose should include resistance exercise forms as well.